Gastric cancer in a situs inversus totalis patient with multiple intestinal and vessel variations related to gastrectomy surgery: A case report and literature review. Issue 39 (September 2017) - Cao, Yinghao; Li, Jiang; Shen, Liming; Wang, Jiliang; Xia, Zefeng; Tao, KaiXiong; Wang, Guobin; Cai, Kailin
Abstract: Rationale: Situs inversus totalis (SIT) is a rare congenital anomaly characterized by complete inversion of the abdominal and thoracic organs, and often involves multiple genetic mutations. The most suitable surgical technique for patients with multiple vessel and organ variations as well as SIT remains unclear. Furthermore, there has been insufficient clinical evidence that demonstrates which surgical techniques achieve the best outcomes. Finally, the standard of care has not yet been determined. We present the case of a 60-year-old man with SIT, who was diagnosed with moderately and poorly differentiated adenocarcinoma at the gastroesophageal junction. We further describe the advantage of using robotic-assisted laparoscopic surgery in patients with this anomaly. Patient concerns: A 60-year-old man complained of pain in his upper abdomen for 3 months. Physical examination revealed an apex beat in the right fifth intercostal space, and vascular anomalies were noted on abdominal angiographic computed tomography. Diagnoses: Moderately and poorly differentiated adenocarcinoma at the gastroesophageal junction with SIT. Interventions: Robot-assisted total gastrectomy with D2 lymph node dissection and hand-sewn Roux-en-Y anastomosis was performed. Outcomes: The postoperative course was uneventful, and the patient was discharged on the seventh postoperative day. Lessons: Robotic surgery for gastric cancer is a safe and feasible alternative to laparoscopic surgery and it can be successfully used to treat gastric cancer in patients with SIT with multiple anatomic variations. As exemplified by our case, SIT might be accompanied by multiple anatomic variations. Detailed preoperative detailed imaging of the blood vessels and gastrointestinal tract is useful in these patients.